Being There and Not Being There: Historiography and the Digital Arts - Worden, Suzette (John Curtin Gallery, Curtin University of Technology, 2002)
Histories of the digital arts have their own distinctive concerns. These interests also deserve to be compared to more general historiographical discussions of history writing where there have been fierce debates about empirical analysis and theoretical developments allied to postmodern linguistic theory. Through this comparison, the ways in which history can be a creative process will be examined.